The impact of the donors’ COVID-19 status on the outcomes of allogeneic hematopoietic stem cell transplantation: a multi-center retrospective study - Huang, Yifei; Fan, Zhiping; Hu, Yingying; Feng, Sizhou; Wang, Shunqing; Zhang, Shanyu; Huang, Fen; Xuan, Li; Xu, Na; Liu, Hui; Wang, Zhixiang; Sun, Jing; et al. (Frontiers in Microbiology, 2024)
To explore the impact of donor COVID-19 status on allogeneic stem cell transplantation (allo-HSCT), we compared the transplant outcomes of the 74 participants including 9 receiving graft from COVID-19 positive donors (CPD), 45 COVID-19 experienced donors (CED) and 20 COVID-19 naive donors (CND) in this multi-center retrospective study. All the apheresis were successful and no significant difference among three groups regarding CD34+ cells or lymphocytes in grafts. All the patients achieved engraftment by day 30 post-HSCT. The incidence of grade II-IV acute graft-versus host disease (aGVHD) were 55.6%, 20% and 10% in the CPD, CED and CND group, respectively (P=0.024). Multivariate analysis showed that COVID-19positive in donor at the time of apheresis was an independent risk factor for II-IV aGVHD (P=0.020, OR=12.159, 95% CI 1.783-135.760). There were no differences in other complications among the three groups in term of chronic GVHD, viral infection or sinusoidal obstruction syndrome. The 6-month overall survival and disease-free survival were also similar among the three groups. Our results suggested that the COVID-19-positive status of donors might not impact graft collection, engraftment or short-term survival of allo-HSCT recipients, but might increase the risk of aGVHD.Further research should be performed to explore the influence of the COVID-19 status of donor on long-term complication and survival in allo-HSCT recipients.